Use of Digital Storytelling (DST) in Public Speaking Subject: An Innovation - Karnedi, Karnedi; Utami, Silvia (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
The present study aimed to find out and describe the effectiveness of using digital storytelling on students' speaking ability in the public speaking subject. Digital storytelling was proposed by Frazel (2010) with three stages: planning, production, and presentation. In this study, the researchers applied a pretest-posttest control group model of experimental research. The population of this research was the fifth-semester English Literature students of STBA Persada Bunda in the academic year 2022-2023. The data were taken from two Public Speaking classes such as Regular A and Regular B class. Speaking tests were used as the key instruments. Digital storytelling was implemented in Regular A as the experimental class, and the conventional method was implemented in Regular B as the control class. The results of the research revealed that the students got lower scores on the pretest, good scores on the mid-test, and very good scores on the final test. After implementing digital storytelling, there was significant progress in students' speaking skills for the experimental class.